10-16x-6-5x=7

Simple and best practice solution for 10-16x-6-5x=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-16x-6-5x=7 equation:


Simplifying
10 + -16x + -6 + -5x = 7

Reorder the terms:
10 + -6 + -16x + -5x = 7

Combine like terms: 10 + -6 = 4
4 + -16x + -5x = 7

Combine like terms: -16x + -5x = -21x
4 + -21x = 7

Solving
4 + -21x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -21x = 7 + -4

Combine like terms: 4 + -4 = 0
0 + -21x = 7 + -4
-21x = 7 + -4

Combine like terms: 7 + -4 = 3
-21x = 3

Divide each side by '-21'.
x = -0.1428571429

Simplifying
x = -0.1428571429

See similar equations:

| -15=-4m+5[5] | | .16(y-3)+.04=.14y-.03(30) | | x+(x*.20)+(x*.10)=5000 | | 12x+1=11x+3 | | 23-p=8 | | 6+5(-7+7v)=146 | | w^2+8w-9=0 | | x+(x-6)=116 | | 10+6=-2(7x-8) | | 85=5(1+4n) | | 12x+9-4x-4=7-x+30 | | 4x+37-6x=3-8x+4 | | 4(3x+7)=-17+21 | | 2(6n+1)=62 | | -8+3x-4=5x+10 | | 12x+4=11x+11 | | 6(3-z)*5=-z | | 9=4p+6-p | | 3x+3=8x+13 | | 200x-1400= | | 4(-3+1)=-8 | | 6q=30q | | y^5-2y^3+y=0 | | 6(3-2x)=42 | | 4(7r+3)=236 | | x+7+x+7-17=17 | | x+7+x+7-17=11 | | 3ln(2x-5)=6 | | 4x^2+8=72 | | 3ln(2x+5)=6 | | 8x-2=6x+12 | | 6x+6+2x=24 |

Equations solver categories